An analysis of the Zimbabwean administrative law in dispute resolution from the period 2008-2015: using Midlands provincial administration office as a case study - Mawonera, Penesia Natasha (Midlands State University, 2017)
The study to be undertaken aims at discovering the enforcement of the Zimbabwean Administrative law in resolving disputes that emerge within the public sector departments to ensure stable provisioning of public services using the Midlands Provincial office as the case study. The absence of development within the public sector departments is as a result of emerging and pending unresolved disputes. It is against this background that the study will focus on whether the Zimbabwean Administrative law related dispute resolution methods are of essentiality in promoting a dispute free environment within the public sector. Hence the objective of this research is to analyse the Zimbabwean Administrative law in dispute resolution. This study will dig into all the dispute resolution methods that have been enforced with aid from the staff within the department of Midlands Provincial Administrator‟s office. Literature review showcased relevant conceptual framework of disputes, types of disputes, types of labour disputes, Zimbabwean administrative law, dispute resolution strategies, differences between the Western and African dispute resolution methods, ways of preventing workplace disputes. An analysis of how dispute and development are related and challenges surrounding effective enforcement of administrative law in dispute resolution in a bid to explore the approaches effectiveness of the Zimbabwean Administrative law. Both qualitative and quantitative approaches were used during the study. Questionnaires and interviews were the core sources of data collection methods usedfrom the workers within the Midlands Provincial Administrator‟s office. The study results showed that the Zimbabwean Administrative law have got loopholes that make it difficult for disputes to be resolved successfully. Results also showed that disputes are triggered by a number of things which need strict and proper recognition of ways to do away with these problems. It has also been noted that though the government have been trying to enforce laws to get rid of disputes but they are ineffective which have made employees lose faith in the government as far as dispute resolution is concerned. So there is need for the government to adopt other resolution methods that are being used by other countries so as to create a development oriented environment.